Instrument Development to Assess University Students’ Coping with Negative Academic Feedback - Özden Turgut; Gürbüz Ocak (Mimbar Sekolah Dasar, 2022)
The students of higher education should perform well enough in academic life. One major problem of academic life is the stress experienced by having high grades. The student who receives a lower grade must cope with this feedback on his performance. Therefore, this study aims at developing an instrument for assessing university students’ coping with negative academic feedback. This scale development research is a mixed-method study that is particularly exploratory sequential pattern. The study group consists of 450 university students. In the conclusion of the analyses, it has been determined that the scale consists of four factors. There were nine items in the first factor, six in the second, five in the third, and seven in the fourth. The scale totally has 27 items. The total Alpha coefficient value of the scale is 0.883. Item-total correlation for the scale is between 0.273 – 0.645. The findings have shown that the factor values are between 0.348 – 0.809. The total variance of the scale has been % 49.471. It is concluded that Coping with Negative Academic Feedback Scale (CNAFS) is a valid and reliable instrument for university students.